Optimization of the Route of Distribution of LNG using Small Scale LNG Carrier: A Case Study of a Gas Power Plant in the Sumatra Region, Indonesia - Budiyanto, Muhammad Arif; Pamitran, Agus Sunjarianto; Yusman, Triana (International Journal of Energy Economics and Policy, 2019)
In this study, the distribution of LNG for power plants in the islands was designed using the Small-Scale LNG Carrier in the Sumatra region of Indonesia. It was further optimized through the use of the Capacitated Vehicle Routing Problem in order to maximize shipload. The research input variables were LNG requirements from receiving terminals, carriers with variations in loading capacity, and distribution distance. The calculation results showed 93 alternative routes with 3 different carrier capacities. The best combination of routes and cargo were found to be 7500 CBM carrier with route Arun - Sabang - Lampung - Arun, 5000 cbm carrier with route Arun - Nias - Belitung - Arun, and 2513 cbm carrier with route Arun - Bangka - Arun. The economic analysis showed that annual USD 74,346,340 CAPEX and USD 33,704995 OPEX at least results in an LNG sales price margin of USD 6.5 per mmbtu. Keywords: Small Scale LNG Carrier, LNG distribution optimization, Capacitated Vehicle Routing Problem. JEL Classifications: L95, R41 DOI: https://doi.org/10.32479/ijeep.8103